Community-Based Tourism (CBT): A Way of Creating and Enhancing the Livelihood of Local People - Hong Long, Pham; Thi Thanh Kieu, Nguyen (VNU Journal of Science: Policy and Management Studies, 2019)
Abstract: Aiming to sustainable development, community-based tourism (CBT) is popular and effective means of the local livelihoods’ enhancement, the preservation of traditional culture values as well as environmental conservation. Therefore, CBT is a form of tourism which has been developed in some remoted areas in Vietnam. The paper explains the role of CBT in the livelihood transformations via tourism activities, analyzes the advantages and disadvantages of CBT development and consequently recommends a number of practical solutions for developing CBT in Vietnam in the forthcoming time. Keywords: CBT, livelihood, local people, Vietnam. References [1] L.L. Nicholls, Elements of community tourism community development planning process. VNR's Encyclopedia of Hospitality and Tourism, 1993, pp. 773-780. [2] B.T.H. Yến, Du lịch Cộng đồng. NXB. Giáo dục Việt Nam, Hà Nội, 2012. [3] DFID, Sustainable Livehoods Framework. Department for International Development, London, 2007. [4] P.E. Murphy, Tourism A Community Approach. International Thomson Business Press, UK, 1997. [5] WWF, Guidelines for Community-based Ecotourism Development. WWF International, 2001. [6] Đ.M. Cương, Phát triển du lịch cộng đồng góp phần xoá đói giảm nghèo theo hướng bền vững, Kỷ yếu Hội thảo Chính sách phát triển Du lịch cộng đồng và đào tạo nguồn nhân lực phục vụ cho phát triển du lịch cộng đồng tại Việt Nam, Hoà Bình, 2018. [7] Đ.T.H. Giang, Nghiên cứu đề xuất giải pháp tăng cường tính bền vững cho hoạt động sinh kế của cộng đồng dân cư tại vườn quốc gia Xuân Sơn, tỉnh Phú Thọ, Đại học Quốc gia Hà Nội, 2017. [8] B.V. Tuấn, Thực trạng và giải pháp đảm bảo sinh kế bền vững cho cộng đồng dân cư ven đô Hà Nội trong quá trình đô thị hóa, Tạp chí Khoa học, Đại học Quốc gia Hà Nội, 31 (5) (2015), pp. 96-108. [9] Công ty Cổ phần Du lịch Cộng đồng Đà Bắc, Mô hình phát triển du lịch cộng đồng ở huyện Đà Bắc, Hoà Bình, Kỷ yếu Hội thảo Chính sách phát triển Du lịch cộng đồng và đào tạo nguồn nhân lực phục vụ cho phát triển du lịch cộng đồng tại Việt Nam, Hoà Bình, 2018. [10] D. Carney, Sustainable rural livelihoods: What contribution can we make?. In Implementing the sustainable rural livelihoods approach, London: Department for International Development, 1998. [11] N.A. Tuấn, Báo cáo dẫn đề, Kỷ yếu Hội thảo Chính sách phát triển Du lịch cộng đồng và đào tạo nguồn nhân lực phục vụ cho phát triển du lịch cộng đồng tại Việt Nam, Hoà Bình, 2018. [12] Ban Chấp hành Trung ương. Nghị quyết 08 của Bộ Chính trị về Phát triển du lịch trở thành ngành kinh tế mũi nhọn. Hà Nội, 2017. [13] P.L. Thảo, Liên kết phát triển du lịch cộng đồng, Kỷ yếu Hội thảo Chính sách phát triển Du lịch cộng đồng và đào tạo nguồn nhân lực phục vụ cho phát triển du lịch cộng đồng tại Việt Nam, Hoà Bình, 2018. [14] M.Isaac, K.Conrad, J.Wuleka, Community-Based Ecotourism and Livelihood Enhancement in Sirigu, Ghana, International Journal of Humanities and Social Science 2 (18), 2012.